Mental Healthcare Reforms in Post-Soviet Russian Media: Negotiating New Ideas and Values - Shek, Olga; Lumme-Sandt, Kirsi; Pietilä, Ilkka (European Journal of Mental Health, 2016)
After the collapse of the Soviet Union, democratic principles began to enter into different branches of Russian social and health policy. As part of these changes, the country demonstrated an intention to develop a new mental health policy based on approaches consonant with the principles of the World Health Organization. This study analyses how these new policy ideas and values are reflected in the Russian mass media, and in particular whether media discourses build upon those ideas or oppose them. It is based on a qualitative analysis of newspapers from the late Soviet period (1980s) through the transition period (1990s) to the present (2000s). The analysis focuses on (1) the protection of patients’ rights, (2) the reorganisation of mental healthcare services and (3) activities preventing stigmatisation. While there was an absence of discussion of mental health problems in Soviet newspapers, the democratic changes of the 1990s triggered the recognition of the existence of mental illness, critiques of Soviet psychiatry and calls for reform. The media response to the new policies was quite ambivalent. Support for patients’ rights and the social integration of the mentally ill was accompanied by fear about the detrimental effects of the reforms on public safety. Articles that challenged stigmatisation also contained negative images of mentally ill people. The media were sceptical about the success of the reforms due to the particularities of Russia’s socio-economic situation and history.